Hereditary sensory and autonomic neuropathy in a family of mixed breed dogs associated with a novel RETREG1 variant. (13th August 2021) - Gutierrez‐Quintana, Rodrigo; Mellersh, Cathryn; Wessmann, Annette; Ortega, Maria; Penderis, Jacques; Sharpe, Samuel; Freeman, Eleanor; Stevenson, Lynn; Burmeister, Louise
Abstract: Background: Hereditary sensory and autonomic neuropathies (HSANs) are a group of genetic disorders affecting the peripheral nervous system. Two different associated variants have been identified in dogs: 1 in Border Collies and 1 in Spaniels and Pointers. Objectives: Clinically and genetically characterize HSAN in a family of mixed breed dogs. Animals: Five 7‐month‐old mixed breed dogs from 2 related litters were presented for evaluation of a 2‐month history of acral mutilation and progressive pelvic limb gait abnormalities. Methods: Complete physical, neurological, electrodiagnostic, and histopathological evaluations were performed. Whole genome sequencing of 2 affected dogs (1 from each litter) was used to identify variants that were homozygous or heterozygous in both cases, but wild type in 217 control genomes of 100 breeds. Immunohistochemistry was used to assess protein expression. Results: Complete physical, neurological, electrodiagnostic, and histopathological evaluations confirmed a disorder affecting sensory and autonomic nerves. Whole genome sequencing identified a missense variant in the RETREG1 ( reticulophagy regulator 1 ) gene (c.656C > T, p.P219L). All affected dogs were homozygous for the variant, which was not detected in 1193 dogs from different breeds. Immunohistochemistry showed no expression of RETREG1 in the cerebellum of affected dogs. One of the affected dogs lived for 5 years and showed gradual progression of the clinical signs. Conclusions and Clinical Importance: We confirmed the diagnosis of HSAN in a family of mixed breed dogs and identified a novel and possibly pathogenic RETREG1 variant. Affected dogs experienced gradual deterioration over several years.